Design, realization, and characterization of a novel diamond detector prototype for FLASH radiotherapy dosimetry. Issue 3 (31st January 2022) - Marinelli, Marco; Felici, Giuseppe; Galante, Federica; Gasparini, Alessia; Giuliano, Lucia; Heinrich, Sophie; Pacitti, Matteo; Prestopino, Giuseppe; Vanreusel, Verdi; Verellen, Dirk; Verona, Claudio; Verona Rinati, Gianluca
Abstract: Purpose: FLASH radiotherapy (RT) is an emerging technique in which beams with ultra‐high dose rates (UH‐DR) and dose per pulse (UH‐DPP) are used. Commercially available active real‐time dosimeters have been shown to be unsuitable in such conditions, due to severe response nonlinearities. In the present study, a novel diamond‐based Schottky diode detector was specifically designed and realized to match the stringent requirements of FLASH‐RT. Methods: A systematic investigation of the main features affecting the diamond response in UH‐DPP conditions was carried out. Several diamond Schottky diode detector prototypes with different layouts were produced at Rome Tor Vergata University in cooperation with PTW‐Freiburg. Such devices were tested under electron UH‐DPP beams. The linearity of the prototypes was investigated up to DPPs of about 26 Gy/pulse and dose rates of approximately 1 kGy/s. In addition, percentage depth dose (PDD) measurements were performed in different irradiation conditions. Radiochromic films were used for reference dosimetry. Results: The response linearity of the diamond prototypes was shown to be strongly affected by the size of their active volume as well as by their series resistance. By properly tuning the design layout, the detector response was found to be linear up to at least 20 Gy/pulse, well into the UH‐DPP range conditions. PDD measurements were performed by three different linac applicators, characterized by DPP values at the point of maximum dose of 3.5, 17.2, and 20.6 Gy/pulse, respectively. The very good superimposition of three curves confirmed the diamond response linearity. It is worth mentioning that UH‐DPP irradiation conditions may lead to instantaneous detector currents as high as several mA, thus possibly exceeding the electrometer specifications. This issue was properly addressed in the case of the PTW UNIDOS electrometers. Conclusions: The results of the present study clearly demonstrate the feasibility of a diamond detector for FLASH‐RT applications.